Approach to patient with cough by American and Chinese respiratory specialist - Xiuxiu Liu; Deniz Kesebir; Mikhail Kazachkov (Elsevier, 2021)
Cough is a common pediatric condition. Acute cough is often considered to be self-limiting and not requiring clinical management. However, pediatric patients and their parents often seek remedies for an acute cough. Traditional Chinese Medicine (TCM) specialists have been treating pediatric cough for millennia. Here we present a case of pediatric cough and the approaches taken to it by a Western and Chinese respiratory specialist. We conclude that TCM may provide important and useful insights into the treatment of such pediatric respiratory disease.